The effect of faecal diversion on human ileum. Issue 6 (17th January 2007) - Williams, Leith; Armstrong, Matthew; Finan, Paul; Sagar, Peter; Burke, Dermot
Abstract : Background: The use of a loop ileostomy is an effective method in protecting pelvic anastomoses. Its use has increased recently, although there is some debate as to the routine use of a stoma. Reversal of the ileostomy is associated with a significant morbidity, which may be related to impaired function of the bypassed distal limb of the ileum. Aim: To investigate the changes that might occur in the distal limb after an interval of faecal diversion. Methods: Full-thickness intestinal circular muscle (CM) strips were prepared from excised loop ileostomies taken at the time of closure. The study sample was from the distal limb and the control from the proximal limb. Contractile activity was measured using an organ bath set up to record isometric contraction after stimulation by acetylcholine (ACh). Histological sections were assessed for an index of villous atrophy, smooth muscle area, and nerve and vessel density. Analysis was with the Wilcoxon signed ranks test for paired data and the Mann–Whitney U test for unpaired data. Results: Samples were acquired prospectively from 35 consecutive patients. The median time between formation and closure of ileostomy was 34 weeks. Significant reduction was observed in the strength of CM contraction, smooth muscle area and median villous index of the distal limb compared with the proximal limb. Conclusion: Impaired intestinal function has been proposed as a contributory factor in the morbidity that may follow closure of loop ileostomy. Significant loss of contractility and smooth muscle strength and villous atrophy occur in the distal ileal limb after faecal diversion. Methods of preventing these changes should be considered.